Treatment of atherosclerotic renal artery stenosis. Issue 3 (May 2009) - Nanjundappa, Aravinda; Dieter, Robert S; Deem, Samuel; Tan, Theodore
Renal artery stenosis (RAS) is an important cause of secondary hypertension. Atherosclerosis remains the leading cause of RAS. RAS leads to reduced renal perfusion pressure and subsequent elevation of neurohormones that accelerate hypertension, congestive heart failure and ischemic nephropathy. Patients with RAS have a low incidence of progressive renal artery occlusion and deterioration of renal function requiring renal replacement therapy. However, patients with RAS have high mortality compared with other patients. This is caused by comorbidities of cerebrovascular disease and coronary artery disease, resulting in stroke and myocardial infarction. The mainstay of treatment for RAS involves maximal medical treatment of atherosclerosis. Renal artery revascularization in patients with significant RAS is recommended for those individuals with uncontrolled hypertensions receiving multiple antihypertensives, and those with flash pulmonary edema, unexplained angina and progressive renal function deterioration. The results of renal artery stenosis revascularization continue to be debatable. The most promising results of renal artery revascularization are noted in hypertension control. Prospective randomized clinical trials, such as the Cardiovascular Outcomes of Renal Artery Atherosclerotic Lesions (CORAL) trial, will hopefully settle the debate of medical treatment versus renal artery stenting for patients with RAS.